Student assessment : fast, frequent, and formative - Dirksen, Debra J. (Debra Jean) (Lanham : Rowman & Littlefield Publishers, Inc., 2014)
In this book, the author provides strategies and techniques, such as the use of graphic organizers, quick writes, and journaling, to be used as formative assessments. Specific information about each tool and recommendations for data analysis and implementation are provided, helping teachers to implement formative assessment effectively and efficiently and allow their students to "preset the reset button" and master the skills they need to be successful in the classroom.
Introduction: Press the Reset Button -- Formative Assessment: Purpose -- Formative Assessment: Reliability and Validity -- Assignments and Assessments -- Preassessments -- Commercial Short-Cycle Assessments -- Collaborative Learning -- Writing -- Graphic Organizers -- Games -- Discussions -- Technology -- Efficiency in Data Collection and Analysis -- Instructional Interventions -- Bringing it all together.
Includes bibliographical references and index.
Keywords: Educational tests and measurements -- United States